FACTORS OF DEVELOPMENT OF NONVERBAL SEMIOTICS IN THE PROCESS OF EDUCATIONAL DESIGN - Abdusamatov Alisher Sobirovich (Scholar Express Journal, 2023)
This article provides information about the fields of semiotics and their boundaries and types, the importance and application of semiotic aspects, necessary pedagogical conditions, scientists and their views, branches, directions and applications of semiotics. in our daily life. Here's how we use it.
Keywords: ecology; nature; ecological education; environment